Development of Neural Networks in the Brain, and Their Possible Evolution - Chang, Yi-Fang (International Journal of Independent Research Studies, 2025)
First, modern neurobiology is introduced. Next, we discuss the nonlinear whole biology and Lorenz mode1 of brain, which can vividly describe the general complementary of left and right brain functions. Third, we research development of neural networks in the brain, in this process the death of some neurons and cells will lead to the loss of certain functions. Such we may compare the differences between children and adults, and can identify these neurons and corresponding functions. Fourth, blind vision and brain plasticity are discussed. Cattaneo, et al., study blind vision that is a great work. Fifth, we search transformations among vision and other sensations, and possible tests. Sixth, we research neural network and quantum neuroscience in interdisciplinary studies. Neurobiology, as a frontier of scientific development, not only has many problems to be solved, but also can greatly improve the conditions for human survival.